Effect of back blow health education with demonstration method on mother's knowledge in first aid for choking children - Muhamad Nur Rahmad; Sigit Yulianto; Nikma Alfi Rosida (Science Midwifery, 2023)
Choking is an emergency condition that can occur at any age, especially in children and infants. This condition can make a person experience a blockage in the respiratory tract so that immediate help is needed because it can make the body experience hypoxia which can lead to death. One of the basic life support measures in first aid for choking patients in children and infants is the backblow method. The sooner victims are found and help is carried out, the survival will increase so that they avoid disability or death. The purpose of this study was to determine the effect of giving backblow education using the demonstration method on mothers' knowledge in first aid for choking children. The research method uses a quantitative method with a quasi-experimental research design - nonequivalent without control group design involving 34 respondents with consecutive sampling. Data were analyzed using SPSS with paired t test or t dependent. The results showed that the average knowledge score before the intervention was 12.68 with a standard deviation of 2.212 while the knowledge score after the intervention was 17.00 with a standard deviation of 1.891. The conclusion is that there is an effect of backblow education with the demonstration method on mother's knowledge in first aid for choking children.